A Novel Method for Fluid Pour-Point Prediction by Molecular Dynamics Simulations. Issue 4 (25th June 2021) - Ahmed, Jannat; Shi, Junqin; Lu, Jie; Ren, Ning; Lockwood, Frances E.; Wang, Q. Jane
Abstract: Pour point, or the temperature below which a fluid ceases to flow, is an important lubricant property. A molecular-dynamics-based approach is developed to explore and identify the pour points of a number of fluids. Diffusion behaviors of several fluids are investigated by time-averaged mean squared displacement (MSD), and a clear trend change of the MSD data is observed as a function of temperature. The temperature at this trend change corresponds well with the experimental pour point. Further, a correlation formula is obtained to link pour point and the ratio of the solvent accessible surface area (SASA), which is defined as the locus surface of the center of a solvent probe when it rolls over the surface of the fluid molecule, to the total number of carbon, in terms of SASA/ Nc, and several molecular structural features. The pour points obtained from the molecular dynamics (MD) simulation and formula prediction are compared with existing experimental results, and the good agreement supports the proposed pour-point determination methods.